Antenatal Noninvasive DNA Testing: Clinical Experience and Impact - Ferres, Millie A.; Hui, Lisa; Bianchi, Diana W. (American Journal of Perinatology, 2014)
Background Nearly two decades ago, the discovery of circulating cell-free fetal DNA in maternal blood created a paradigm shift in prenatal testing. Recent advances in DNA sequencing technology have facilitated the rapid translation of DNA-based testing into clinical antenatal care.Content In this review, we summarize the technical approaches and current clinical applications of noninvasive testing using cell-free DNA in maternal plasma. We discuss the impact of these tests on clinical care, outline proposed integration models, and suggest future directions for the field.Summary The use of cell-free DNA in maternal blood for the detection of fetal rhesus D antigen status, fetal sex, and common whole chromosomal aneuploidies is now well established, although testing for aneuploidy is still considered screening and not diagnostic. Further advances in technology and bioinformatics may see future clinical applications extend to the noninvasive detection of fetal subchromosomal aneuploidy, single gene disorders, and the entire fetal genome.
Keywords: cell-free fetal DNA; prenatal screening; noninvasive prenatal testing; NIPD; NIDT; pregnancy